THE INFRASTRUCTURE OF THE NATIONAL INNOVATION SYSTEM (Journal of Economic Research & Business Administration, 2017)
The article is devoted to one of the most urgent problems of Kazakhstan’s economy – innovation infrastructure. In the presented work approaches to the definition of the concept of «innovative infrastructure» of various authors, legal sources, including Kazakhstan ones, are considered. The institutes that form the innovative infrastructure in the Republic of Kazakhstan are determined. Key trends in the development of innovative infrastructure are identified at the present stage of its formation in our country. The article gives different views on the components of the innovation infrastructure and considers it necessary to introduce additional elements such as the commercialization of intellectual property and state regulation of innovation and its infrastructure. The text refers to the total number of elements of the innovation infrastructure, the number of its individual elements.